Vibration cancellation of semiconductor manufacturing robots. (April 2015) - Wang, Zining; Wang, Cong; Tomizuka, Masayoshi
Abstract: The semiconductor manufacturing industry is having a critical upgrade. To meet the new standards of silicon wafer production and processing, vibration control of wafer handling robots must break new grounds because conventional methods have reached their limits. This paper presents a direct vibration cancellation method for semiconductor manufacturing robots. With a vibrotactile transducer on the wafer holder, the vibration can be significantly reduced without adversely affecting the tracking accuracy of the wafer handling motion. Several control strategies are analyzed and combined to obtain the best performance. Experimental validation shows a vibration reduction of 47% in energy and 30% in amplitude.